2023
DOI: 10.1177/10668969231152586
|View full text |Cite
|
Sign up to set email alerts
|

EBV-negative Fibrin-Associated Large B-Cell Lymphoma Arising in Thyroid Hyperplastic Nodule: Report of a Case and Literature Review

Abstract: Fibrin-associated large B-cell lymphoma is a rare microscopic-sized tumor, typically representing an unexpected finding at sites rich in chronic fibrin deposition. It is associated with Epstein-Barr virus, and has been reported to occur in a wide variety of anatomic sites and clinical scenarios. We report a case arising in a thyroid hyperplastic nodule, only the second case reported in this location. Notably, this is only the fourth case of fibrin-associated large B-cell lymphoma that is not associated with Ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
(61 reference statements)
1
1
0
Order By: Relevance
“…However, chronic inflammation in a fibrin-rich microenvironment probably plays a critical role in type III EBV latency (13). Like our patient, 95.4% of previously published FA-DLBCL cases were related to EBV (7), supporting that FA-DLBCL is an EBV-associated large B-cell lymphoma.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…However, chronic inflammation in a fibrin-rich microenvironment probably plays a critical role in type III EBV latency (13). Like our patient, 95.4% of previously published FA-DLBCL cases were related to EBV (7), supporting that FA-DLBCL is an EBV-associated large B-cell lymphoma.…”
Section: Discussionsupporting
confidence: 72%
“…Herein, we described a rare case of FA-DLBCL arising in a retroperitoneal pseudocyst. Ho et al (7) summarized 87 patients with FA-DLBCL. Their literature review revealed that patients with FA-DLBCL had many types of underlying medical conditions, such as cardiac myxoma, thrombus, hematoma, aneurysms, prosthetic valves, breast implants, and cystic lesions at various locations (8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%